Genomic characterization and fermentation study of the endophyte Stemphylium sp. (Aa22), a producer of bioactive alkyl-resorcinols - Jorge Rojas López-Menchero; Juan Imperial; Maria Fe Andrés; Carmen Elisa Díaz; Azucena González-Coloma (PLoS ONE, 2025)
The genome of the previously described endophytic fungus Stemphylium sp. (strain Aa22) has been sequenced to near completion. Phylogenomic analysis placed strain Aa22 in close proximity to Stemphylium lycopersici. Strain Aa22 had been previously reported as the producer of the bioactive alkyl-resorcinol stemphol and derivative stempholones A and B in solid culture on rice. Genome mining for biosynthetic gene clusters (BGCs) identified 38 genomic regions predicted to encode secondary metabolites production. Among them, a single type III polyketide synthase (T3PKS) that shared similarity with other fungal T3PKSs was identified. T3PKSs are responsible for the biosynthesis of alkyl-resorcinols from fatty acyl-CoA substrates. This makes the identified T3PKS gene a likely candidate for stempholone biosynthesis and a target for future manipulation to enhance production of bioactive alkyl-resorcinols. We also studied the production of these compounds in solid rice media and in liquid PDB medium with or without the addition of talcum powder. The highest extract yield was obtained with PDB cultures, and GC-MS analysis revealed the presence of high levels of the bioactive compound stempholone A, along with two unidentified compounds. Addition of talcum powder suppressed stempholone A production and reduced chemical diversity, with accumulation of oleamide. In contrast, the rice solid media fermentation resulted in methylated fatty acids and oleamide, with no detectable stempholone.